Online Merchandising and Its Impact on Customer Behavior: Analysis of ASOS, H&M, and FOREVER21 - Khamlichi, Farah (2012)
The number of businesses that sell their products on the internet is constantly increasing and customers find themselves with a wide choice of web sites to shop from so online retailers consider seriously web merchandising for their web based stores in order to offer better and different services / products from rivals and therefore be able to attract customers and affect their purchase intention. We deepen in the topic of online merchandising and its impact on customer purchase behavior through the analysis of three apparels web sites which are ASOS, H&M, and FOREVER21. The dissertation starts with a general introduction of the topic and the research question. Then, the literature review provides a detailed explanation of the main concepts of online merchandising. After that, the analysis section of the three online stores results in some important themes including the importance of having a well organized web site layout to assist customers through their navigation. Last, the conclusion shows that further improvement in merchandising are needed for these online stores in order to enhance customers shopping experience since they still have a lack of some important features of merchandising tools.